Persepsi Siswa terhadap Hasil Belajar dalam Pemanfaatan Media Pembelajaran Interaktif Kahoot Bahasa Indonesia Teks Deskripsi - Sahrul Mubarok; Asep Purwo Yudi Utomo; Mu’allimatin Najihah; Alfiyani Nur Safitri; Ngabiyanto Ngabiyanto; Galih Suci Pratama; Fitrianita Utami (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the most important things in the teaching and learning process is learning that is creative and fun because it can help students to succeed in learning. For a teacher, mastery and knowledge in utilizing technology is a competency that must be mastered in order to support the improvement of the learning process and the delivery of material to students. Facts on the ground show that Indonesian language teachers still use conventional learning method as well as the use of technology which is limited to using LCD media and laptops to convey material and give assignments. In addition, smartphones have not been used optimally as learning media. The purpose of this study was to determine students' perceptions of the use of Kahoot-based interactive learning media on learning outcomes. This research was total sampling basis are all number of the population are used as samples. The samples of this research involves 30 people. Data collection used in this research is questionnaire. This study used a quantitative approach and data were analyzed using an independent sample t-test to determine the level of Kahoot application as an interactive learning media for Indonesian subjects in descriptive text material. The results showed that students tended to have very good perceptions of 46.67% regarding the use of Kahoot media in learning Indonesian. The benefit of this research is to provide additional knowledge and information to teachers, especially Indonesian language educators, in the use of Kahoot-based interactive learning media.